Why Do Physicians Prescribe Antibiotics? A Systematic Review of the Psycho-Socio-Organisational Factors Related to Potentially Inappropriate Prescribing of Antimicrobials in Europe - Chiara Lansink; Bhanu Sinha; Nico Meessen; Tessa Dekkers; Nienke Beerlage-de Jong (MDPI AG, 2024)
Purpose: Effective antimicrobial use enhances care quality and combats antibiotic resistance. Yet, non-guideline factors influence potentially inappropriate prescribing. This study explores psycho-socio-organisational factors in antimicrobial prescribing as perceived by physicians across primary, secondary, and tertiary care. Methods: Adhering to PRISMA guidelines, a systematic review was conducted using PubMed and Scopus databases from 1 January 2000, to 8 March 2023, with an update search until 30 January 2024. Inclusion criteria focused on studies in Europe exploring psycho-socio-organisational factors for antibiotic prescribing from physicians' perspectives in hospital, inpatient, or primary care settings. Exclusion criteria targeted out-of-office prescriptions or low-quality studies. To evaluate the latter, several quality and risk-of-bias checklists were used. Data were extracted on study characteristics, study design, and methods and identified determinants of antibiotic prescribing. Data was analysed using a narrative synthesis method. Results: Among 8370 articles, 58 met inclusion criteria, yielding 35 articles from 23 countries. Three main themes emerged: personal, psychological, and organisational factors, encompassing seven determinants including work experience, knowledge, guideline adherence, uncertainty management, perceived pressure, time constraints, and diagnostic resource availability. Uncertainty management was key, with work experience and knowledge mitigating it. No additional factors emerged in the updated search. Conclusion: Enhanced uncertainty management decreases perceived patient and/or parental pressure to prescribe antibiotics, contributing to reducing potentially inappropriate prescribing (PIP). Therefore, it is imperative to educate physicians on effectively managing uncertainty. Interventions to improve antibiotic prescribing should be tailored to the specific needs and preferences of the different prescribing physicians.